The Pandemic Olympics: A Thematic Analysis of COVID-19 and the Tokyo Olympic Games from a Canadian Perspective - Stead, Aiden George (Université d'Ottawa / University of Ottawa, 2022)
Hosting the Tokyo 2020 Olympics during the COVID-19 pandemic presented a major crisis for the Olympic movement, both in Canada and around the world. The Pandemic led to an unprecedented postponement of the games and to widespread concern that the Tokyo Olympics could become a mega-spreader event. The purpose of the present study is to provide an empirical accounting of the Canadian experience prior to and during the Tokyo Games, specifically through a thematic analysis of content related to COVID-19 and the Olympic Games, as produced by major Canadian media sources and key Canadian sport organizations. Utilizing a communication centered view of crisis informed by Situational Crisis Communication Theory (SCCT) and narrative management, the present study examined the crisis response of major Canadian sport organizations, most specifically the Canadian Olympic Committee (COC) (Coombs, 2007; DiSanza et al., 2018; Gigliotti, 2020). A unique methodological approach was used in the present study, beginning with both database and grey literature search strategies to collect data from Canadian media sources and sport organizations. Sources included the CBC, the National Post, and the Globe and Mail as media sources, and the Canadian Olympic Committee, Own the Podium, and Sport Canada as major sport organizations. Researchers then followed a data analysis process utilizing a framework of thematic analysis from Braun and Clarke (2006), collaborative analysis following Richards and Hemphill (2018), and the use of software and visual narrative analysis based on the work of Hoeber et al. (2017). This methodology allowed the researchers to analyze a large sample of 930 documents published between March 11th, 2020 and August 22nd 2021. The results of the present study revealed a complex and changing narrative in response to the COVID-19 pandemic and subsequent postponement of the Tokyo Olympics. The decision by the COCC to withdraw from the Olympics in March 2020 was portrayed as a principled stand that influenced the IOC into postponing the Games to a year later. The COC continued to focus on promoting athletes in their public messaging and presented a strong, coherent narrative that appeared consistent with the values of key stakeholders and minimized the reputational threat posed to the organization. The IOC however received substantial negative media coverage, especially in the lead up to the Games in 2021. During the initial period of the Games themselves, media coverage focused on new COVID-19 cases and the effect of strict safety protocols. However, by August 2021 there appeared to have been a significant shift in the narrative, with the focus becoming stories and performances of Olympic athletes. The results of the present study emphasize the importance of effective narrative management in crisis communications, and the consistently of this approach with SCCT (Coombs, 2007; DiSanza et al., 2018). Furthermore, the effectiveness of the COC’s crisis response also reinforces a communication centered view of crisis, where the perceptions of stakeholders are viewed as a key element of defining organizational crisis management (Gigliotti, 2020). To minimize the reputational threat to their organizations, crisis managers should ensure that stakeholder perceptions remain central to their crisis communication decision making, and managers should also consider the importance of crafting a strong and coherent narrative.
Keywords: Communication centered view of crisis; Canada; Tokyo 2020; Olympics; Crisis Communication; Narrative; Situational Crisis Communication Theory; Narrative management